Banking and Accounting Issues - Mohammad Alsharari, Nizar (IntechOpen, 2022)
The influx of new information technologies with dynamic changes is one of the greatest business threats nowadays. Accordingly, international business and academia have claimed to be working towards developing innovations in accounting and finance that are useful for all stakeholders. The recent accounting and finance scholarship has moved forward toward new innovations that advanced professional practice. This book introduces and discusses new innovations in accounting and finance, including management accounting, blockchain, E-business models, data analytics, artificial intelligence, cryptocurrency, bitcoin, digital assets, and associated risks. It also sheds light on how and why accounting and finance innovations have changed over time. As such, it is a useful resource for individuals working in accounting and finance.